Nature's early warning system can serve us well - Abd Razak, Dzulkifli (2005)
A Friend returned from Banda Aceh last week telling how horrible the situation is there. People are dying daily, sometimes in the most tragic way, such as the child who died from choking on too much mud. This happened while world leaders were warning system - although some claim that it is not entirely foolproof. On hindsight, it is strange that we are how talking about an early warning system (EWS), when the system is around us every day, that is, Mother Nature herself. Going by some of the anecdotes related after the tsunami, this point has been totally missed.